A Meta-Analysis of Research on the ‎Effectiveness of Constructivist Learning at ‎Yarmouk University between 2010 and 2021 ‎in Science Education and Its Impact on ‎Learning Scientific Concepts ‎ - Al-Azzam ‎, Sulaf; Banikhalaf, Mahmoud (Jordan Journal of Educational Sciences, 2024)
The current study aimed at reviewing research that dealt with the effectiveness of using constructivist learning in science education at Yarmouk University from 2010 to 2021and its effectiveness in learning scientific concepts. To achieve the aims of the study, a meta-analysis was conducted. The study sample consisted of 23 university theses and dissertations, and used a code model for data collection. The study’s findings indicated that effect sizes were not uniform, so the researchers had to apply the random effects model. The results showed that effect of the constructivist learning on learning scientific concepts was statistically higher (Effect size=1.81) in the random-effects model. A heterogeneous distribution was obtained from the sample. The meta-analysis found no statistically significant differences in the effect sizes of academic level variables at the master’s degree dissertation level, study field variables in biology, the duration of using the study tool (9–122 weeks), or gender variables at different levels (male, female, or male-female). There were no statistically significant differences in the effect sizes of educational level variables